Interpersonal Communication that Inspires in EFL Teaching - Muhammad Amin Rasyid (ELT Worldwide: Journal of English Language Teaching, 2015)
This study attempted to reveal the perception of EFL students on the lecturer verbal and nonverbal interpersonal communication that they experience and expect to foster their positive attitudes and nurture their motivation in learning English at State University of Makassar, Indonesia. The respondents consisted of 152 fifth semester students of undergraduate program, majoring in English Education, attending TEFL course in 2013/2014 academic year. The study was guided by the researchers’ teaching belief stating that teaching is communicating and inspiring virtues in the forms of knowledge, skills and attitudes. The instruments used were (a) The 14 lecturer verbal interpersonal communication  measure (VICM) and (b) the 14 lecturer non-verbal interpersonal communication measure (NVICM) developed by the researcher. The data analysis showed that four of the 14 VICM were not inspiring, namely telling students his personal experience, responding students’ reasons for being late, asking students to tell their most impressive learning English experience, and  allowing students to call their lecturers by their first name; and three of the 14 NVICM were not inspiring, namely moving around the class when teaching, touching (shaking hands), coming closer to students when lecturing. Key concepts: perception, inspiring, interpersonal, communication